Human Values among College Students (Case Study in Chikodi Taluk): The Decline and Transformation of Human Values among College Students (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Human values are the virtue that guide to every one individual to lead good personal, social and public life .These values are considered as the guide lines to lead suitable good life In ancient society human values takes place in higher priority and individual inculcate in their day hesitation values come in to existence in every one’s life.Now in modern era these values become weaker because of less followers. In changing society youths are given less importance to follow the values in their life they think modern independent values are most important in the place of old human values. Honesty, Respect, Empathy, Listening, Appreciation, Affection, Openers, Love towards all human being are good values which are followed by everyone in our society.